2011年1月に観測されたバレンツ海上のポーラーロウの数値実験 - 三井, 拓; 猪, 上淳; 堀, 正岳; 万田, 敦昌; Taku, Mitsui; Jun, Inoue; Masatake, E. Hori; Atsuyoshi, Manda (2013)
Variability of sea-ice extent over the Barents Sea is one of the important factors to predict the Japanese winter coldness. The mechanism strongly depends on cyclone activities at the marginal ice zone over the Barents Sea (Inoue et al. 2012). In January 2011, we conducted observations over the Barents Sea with the aid of the Norwegian R/V Johan Hjort, and succeeded in observing a polar low developed along the marginal ice zone on January 22nd. In this study, we conducted numerical experiments using a regional atmospheric model for elucidating the relationship between the polar low development and sea ice distribution. The target period is from 00UTC on 20th January to 00UTC on 25th January 2011. The model domain covers surrounding the Barents Sea sector (2,800km x 2,000km) with 10km horizontal resolution and 38 vertical layers. ERA-Interim reanalysis is used as the initial and boundary conditions. We conducted two sensitivity experiments for evaluating the influence on the area of sea-ice by replacing surface boundary conditions. ICE_HY (heavy year) and ICE_LY (light year) used the observed sea-ice concentration and SST on January 20th in 2004 and 2006, respectively. Comparing with the observed temperature vertical profile and shipboad sea level pressure (SLP) time series, the tropopause fold and a sudden drop in SLP were well reproduced. SLP was about 5hPa fallen for ICE_HY with ICE_LY at 00UTC 24th January, we elucidated the development of polar low of ICE_LY (Fig. 1). To understand this development, we conducted Dry experiments for ICE_HY and ICE_LY to consider effect of condensate heat. As a result of comparison of the time series of eddy kinetic energy, contribution of condensation heat is much large. 第4回極域科学シンポジウム 個別セッション：[OM] 気水圏 11月14日（木） 統計数理研究所 ３階セミナー室１（D305） conference object